Examine The Factors that Affect the Win-win Strategy for Both Foreign and Chinese Banks Coexistence in Chinese Banking Market - Zhang, Tao (2007)
Abstract Currently, the world has entered into an era of globalization. Almost all industries must have the ability to survive in this era. Banks are not an exception. China, as a fast developing country, attracts more and more foreign banks to set up branches there to make profit in that densely-populated country. But the culture in China is different from Western countries, so if the foreign banks entered, they must know how to deal with cultural differences. The author wanted to make a contribution in this area. The first part, the Critical Literature Review, emphasised the basic concepts of the relative terminologies, such as globalisation, Customer Relationship Management, the characteristics of Chinese culture, mainly the importance of Guanxi. In the Critical Application Review, the author mentions the current methods that banks use to attract and maintain customers and gives some suggestions based on Chinese culture.